The relationship of the North American Monsoon to tropical and North Pacific sea surface temperatures as revealed by observational analyses - Castro, Christopher Lawrence, author; McKee, Thomas B., author; Pielke, Roger A., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 2000)
The North American Monsoon is a seasonal shift of upper and low level pressure and wind patterns which brings summertime moisture into the Southwest United States and ends the late spring wet period in the Great Plains. The climatology and interannual variability of the North American Monsoon are examined using the NCEP/NCAR Reanalysis (1948-98). The diurnal and seasonal evolution of 500-mb geopotential height, integrated moisture flux, and integrated moisture flux convergence are constructed using a five-day running mean for the months May through September. All of the years are used to calculate an average daily Z-score which removes the diurnal, seasonal, and intraseasonal variability. The average Z-score centered about the date is correlated with three Pacific SST indices associated with the El Niño Southern Oscillation (ENSO) and the North Pacific Oscillation (NPO). These indices are: Niño 3, a North Pacific index, and a North American Monsoon index (M) which combines the previous two. Regional time evolving precipitation indices for the Southwest and Great Plains, which consider the total number of wet or dry stations in a region, are also correlated with the SST indices. The new reanalysis climatology reveals: the time of maximum northward extent of the monsoon is late July, a diurnal cycle in atmospheric moisture which reflects the evolution of summer thunderstorms, the presence of the Baja and Great Plains low level jets, and the seasonal dependence of atmospheric moisture on monsoon ridge position. These results are in agreement with previous, more comprehensive reanalysis climatologies using shorter lengths of record. Pacific SSTs are related to a sequence of teleconnection patterns over North America through the summer. The relationship to the atmospheric circulation is strongest at monsoon onset, when the Pacific Transition pattern controls the large-scale distribution of moisture across the western U.S. A high (low) NPO phase and El Niño (La Nina) conditions favor a trough (ridge) over the northern Rocky Mountains, northern Great Plains. In the Great Plains the spring wet season is lengthened (shortened) and early summer rainfall and integrated moisture flux convergence are above (below) average. In the Southwest monsoon onset is late (early) and early summer rainfall and integrated moisture flux convergence are below (above) average. Relationships with the Pacific SST indices decay in the later part of the monsoon. These idealized climatological responses associated with high and low values of the M index were observed in the Midwest Flood of 1993 and the Drought of 1988, respectively. Tropical and North Pacific SSTs are related to atmospheric moisture and precipitation in the western U.S. to varying degrees depending on location. In the Great Plains, North Pacific SSTs are dominant factor, while in the Southwest tropical and North Pacific SSTs are equally important. Though the M index is the better diagnostic for North American Monsoon, only the time-coincident relationships with atmospheric circulation and moisture are statistically significant. A statistically significant relationship exists between spring Niño- 3 and the atmospheric circulation pattern over North America at monsoon onset.
April 2000.
Keywords: Monsoons -- North America; Ocean temperature -- Tropics; Ocean temperature -- North Pacific Ocean; Climatology -- Observations